KELEMBAGAAN EKONOMI DALAM PRODUKSI BERAS ORGANIK (On Farm – Off Farm) DI JEMBER (Economic Institution Of Production Organic Rice (On Farm – Off Farm) in Jember) - FAJAR WAHYU PRIANTO; LILIANA DWI LESTARI; AGUS LUTHFI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2022)
This study aims to analyze the business of organic rice farming in farmer groups and to analyze institutions, calculate the profits of organic rice farming, social capital and distribution channels of organic rice in farmer groups. The research was conducted for 2 months starting from April to May by means of interviews and direct observation to the research site. The data analysis technique used is the production cost approach to calculate the income of organic rice farming and the institutional role of the Tani Jaya II Cooperative for organic rice farmers in Rowosari Village, Sumberjambe District, Jember Regency. The results of this study indicate that organic rice farming is said to be efficient, social capital can support the sustainability of farming and distribution on organic rice farming is more profitable if it is sold to Koperasi Tani Jaya II because cooperatives  can buy rice at a higher price than collectors and business partners of rice farming businesses. Organic rice in Jember Regency with the Jaya II farmer group has very good potential due to the high demand for organic rice from several companies.